2016
DOI: 10.3390/su8010097
|View full text |Cite
|
Sign up to set email alerts
|

The Building Fabric Thermal Performance of Passivhaus Dwellings—Does It Do What It Says on the Tin?

Abstract: Abstract:The Passivhaus (or Passive House) Standard is one of the world's most widely known voluntary energy performance standards. For a dwelling to achieve the Standard and be granted Certification, the building fabric requires careful design and detailing, high levels of thermal insulation, building airtightness, close site supervision and careful workmanship. However, achieving Passivhaus Certification is not a guarantee that the thermal performance of the building fabric as designed will actually be achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Surveys of a modest sample of Passive House buildings were carried out in-situ [49] and supported the conclusion of research identified earlier that the Passive House standard was robust and gave predictable savings. Research has also shown however that some Passive House dwellings have exhibited some more marginal outcomes [50] and that there is some lack of information in published sources about performance.…”
Section: Review Of Previous Researchmentioning
confidence: 67%
See 1 more Smart Citation
“…Surveys of a modest sample of Passive House buildings were carried out in-situ [49] and supported the conclusion of research identified earlier that the Passive House standard was robust and gave predictable savings. Research has also shown however that some Passive House dwellings have exhibited some more marginal outcomes [50] and that there is some lack of information in published sources about performance.…”
Section: Review Of Previous Researchmentioning
confidence: 67%
“…I3 thought that for architects and associated designers, the use of the PHPP [49] enabled those professionals to see and to demonstrate value in their designs, and thus provide a reason to expend money achieving it. PHPP was an aid to support the businesses of recognized low energy designers as well as to others with a passing interest trying to understand what was required.…”
Section: Financial Costs and Benefitsmentioning
confidence: 99%
“…Whilst such dwellings have been successfully tested [57], they carry higher inherent risk and increased relative uncertainties-particularly from unstable internal temperatures and underestimated HTCs due to stored solar components [56]. Whilst this could mean extended testing durations are required (e.g., 6-8 weeks [37]), longer tests are unlikely to reduce any bias and shorter, highly selective periods are likely to yield improved results.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 7 timber dwellings reported deviations in the range of 6-21% in 6 of the cases [51]; similarly, the fabric performance gap of 3 timber and masonry was found to vary from 6 to 18% [46]. Higher HLC values than calculated have been identified also in Passivhaus constructions, although the gap is generally of a lower magnitude.…”
Section: @50mentioning
confidence: 97%
“…It is defined as air leakage rate per hour per square metre of envelope area at a test reference pressure differential across the building envelope of 50 Pa. Accordingly, it is an inherent influencer of heating and [44] 6 ✓ × ✓ Gupta R, Kapsali M. 2015 [61] 6 ✓ ×× Johnston D, Siddall M. 2016 [51] 7× × ✓ AIMC4 2014 [41] 17 [40] 44 ✓ ✓ ✓…”
Section: Methods and Datamentioning
confidence: 99%